Afro-Argentines of Buenos Aires in the 20th Century: The Suburbanization Process (Quinto Sol, 2020)
If Argentina defines itself as a “White-European” country, its capital, Buenos Aires, presents itself to the world as the epitome of Latin American Europeanness. In the twentieth century, its Whiteness was achieved in part through a process of suburbanization that involved the moving of the Afro-Argentines who lived in the center of the city to its margins or to the Greater Buenos Aires area. The objective of this article is to study this process of Afro-Argentine suburbanization, a topic that has not yet been investigated. We will follow the trajectories of three Afro-Argentine families throughout the last century, paying attention to the active role of state policies in their movements. We will also focus on how the families recall their ways of living in each period, generally shaped by poverty, and on how official policies affected communal practices of sociability that nevertheless endured. To do so, we will rely on archival documents, ethnographic work, and oral history.
Keywords: afro-argentines; suburbanization; state policies; family trajectories